The prevalence and associated factors for anaemia in school children in Bengaluru, Karnataka, India: a cross-sectional study - Safder Husain; Arish Mohammad Khan Sherwani (Health for All Nations, 2023)
Background and Objective: Anaemia is a common clinical condition that affects the majority of school aged children. Reduced resistance to disease, increased susceptibility to infection, impaired physical development, and poor school performance are all consequences of anaemia in this group. The present study was designed with the objective of estimating the prevalence of anaemia among school children in Bengaluru. This included identifying the associated factors or causes and consequences of anaemia. Methods: A school based cross-sectional study was conducted among children in schools from 3rd to 8th standard in Bengaluru Urban North Division Karnataka State, India, over a period of one year. 250 children were selected using convenience sampling. Results: The overall prevalence of anaemia among school going children was found to be 21.2%. Prevalence of anaemia was significant among variables like socioeconomic status, dietary habits, increased heart rate, breathlessness, lack of energy, dizziness, irregular menstrual cycles, jaundice, blood loss during menstruation, menstrual cycle pattern, pallor signs of palpebral conjunctiva, mucous membrane, and skin, splenomegaly and hepatomegaly, consumption of chicken, fish, citrus fruit, milk, Mizāj 'Ām (overall mizaj of body, specifically choleric) duration of menstrual flow, headache, poor wound healing, and chronic disease. Conclusion: The overall prevalence of anaemia in our study of school children in Bengaluru (21.2%) was lower than the prevalence in the data recently shown by NFHS-5. Prevalence of anaemia was highly significant among variables like low socioeconomic status, dietary deficiencies, blood loss, and chronic infections. There were also highly significant correlations with several clinical findings.